Case report: Basivertebral nerve block during vertebral augmentation: an alternative approach to intraprocedural pain management - Santoro, Giovanni C.; Kulkarni, Siddhant; Dhillon, Diljot; Lien, Kenny (Frontiers in Radiology, 2023)
Osteoporotic compression fractures can be treated with vertebral augmentation. Since intraprocedural pain is common during vertebral body endplate manipulation, these procedures are often performed with conscious sedation or general anesthesia. Research has shown that vertebral endplates are innervated by the basivertebral nerve (BVN), which has been successfully targeted via radiofrequency ablation to treat chronic vertebrogenic lower back pain. With this physiology in mind, we evaluated if temporary BVN block would provide sufficient analgesia so that patients could forego sedation during percutaneous vertebral augmentation. Ten patients with single-level vertebral compression fractures were selected. Prior to balloon augmentation, temporary intraosseous BVN block was achieved using 2% lidocaine injection. All ten patients successfully completed their procedure without intraprocedural sedative or narcotic medications, and without significant deviation from baseline vital signs. Temporary BVN block can be used as intraprocedural anesthesia in select patients who may be poor candidates for general anesthesia or conscious sedation.